Advancing proton-conducting ceramic electrochemical devices: perspectives on benchmarking and barriers to progress - Meisel, Charlie; Kim, You-Dong; Diercks, David; O’Hayre, Ryan; Sullivan, Neal P. (Frontiers in Energy Research, 2025)
Proton-conducting ceramic electrochemical devices (PCCs) show promise for sustainable energy conversion, yet key challenges remain. This perspective highlights critical areas for advancing PCC research. The field requires standardized protocols for fabrication, testing, and results reporting. Improved electrolyte sintering techniques and minimized nickel-induced defects are imperative for stable, high-performing cells. Addressing materials criticality is essential for commercialization. A deeper understanding of electrolyte grain boundary properties, positrode-electrolyte interface characteristics, and distribution of relaxation times analysis has great potential to accelerate progress. The promising application of PCCs in electrolysis mode remains understudied and merits increased research attention.